2017
DOI: 10.1186/s40795-016-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary patterns with the fecal microbiota in Korean adolescents

Abstract: Background: The gut microbiota has emerged as an important environmental factor associated with obesity, type 2 diabetes, and cardiovascular disease, through its interactions with dietary factors. Therefore, we analyzed the composition of the fecal microbiota and levels of biochemical markers related to metabolic disease according to dietary pattern in Korean adolescents. Methods: We collected fecal samples from 112 student subjects aged 13-16 years with sufficient information available regarding clinical biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…Past studies suggest that high-fat diets increase the abundance of Prevotella, whereas plant-based diets and fermented foods result in the opposite. 18 As general advice, frequent snacking between meals may cause dysbiosis and so should be kept to a minimum and only constitute fruit and vegetables, if required. The impact of probiotics should also be investigated.…”
mentioning
confidence: 99%
“…Past studies suggest that high-fat diets increase the abundance of Prevotella, whereas plant-based diets and fermented foods result in the opposite. 18 As general advice, frequent snacking between meals may cause dysbiosis and so should be kept to a minimum and only constitute fruit and vegetables, if required. The impact of probiotics should also be investigated.…”
mentioning
confidence: 99%
“…Enterobacteriaceae is a representative family of proteobacteria and is often positively related to the occurrence and development of colitis (Sasaki et al, 2020). Bacteroidaceae is generally considered to be an important member of a healthy microbial community and is associated with dietary fiber intake (Jang, Choi, Kang, Park, & Lee, 2017). Therefore, the decrease of Enterobacteriaceae and the increase of Bacteroidaceae after intervention with POL was a favorable trend for intestinal health.…”
Section: Dietary Pol Alleviated Dss-induced Gut Microbiota Disordermentioning
confidence: 99%
“…Previous studies in 57 unique animal species related to Bacteroidales S24-7 showed that 96% of the animals harboring Bacteroidales S24-7 were herbivores or omnivores mainly consuming herbivorous food (Ormerod et al, 2016). Similar to Bacteroidales S24-7, members of Bacteroidaceae were enriched in the gut systems of Korean adolescents, who consumed mainly plant-based and fermented foods (Jang et al, 2017). Members of the dominant genus Bacteroides are among the most common taxa of the human gut bacterial community (Ramakrishna, 2013).…”
Section: Resultsmentioning
confidence: 99%